2008
DOI: 10.1139/l08-069
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on slotted rectangular and square hollow structural section (HSS) tension connections

Abstract: An experimental study has been carried out on slotted hollow structural section (HSS) connections with and without welding at the end of the gusset plate. A total of 30 slotted square and rectangular HSS specimens, with 16 different connection configurations, were investigated for effects of weld length ratio, slot orientation, gusset plate thickness, slot opening length, and end welding. Experimental results show that the net section efficiency of the specimen with no end welding was greater than unity for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The geometric and material variables for the test specimens are listed in columns 2 through 8 of Table 1, and the experimental rupture load, P e , is listed in column 9. The specimens tested by Zhao et al (2008), Korol et al (1994), andYeomans (1993) were loaded statically, and the specimens tested by Han et al (2007) and Yang and Mahin (2005) were loaded cyclically to simulate seismic loading.…”
Section: Data Analysis Existing Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The geometric and material variables for the test specimens are listed in columns 2 through 8 of Table 1, and the experimental rupture load, P e , is listed in column 9. The specimens tested by Zhao et al (2008), Korol et al (1994), andYeomans (1993) were loaded statically, and the specimens tested by Han et al (2007) and Yang and Mahin (2005) were loaded cyclically to simulate seismic loading.…”
Section: Data Analysis Existing Datamentioning
confidence: 99%
“…The relevant geometric parameters for slotted HSS connections are the wall thickness and weld length. Wall thickness measurements for the 30 ASTM A500 Grade C specimens tested by Zhao et al (2008) resulted in a mean measured-to-nominal thickness ratio of 0.924. Using a design wall thickness equal to 0.93 times the nominal wall thickness according to AISC Specification Section B4.2, the mean measured-to-design thickness ratio is 0.994, with a coefficient of variation of 0.00710.…”
Section: Reliability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng and Kulak (2000) also suggested that the reduction of the effective net area (due to shear lag) would be eliminated for slotted CHS connections if a minimum weld length ( L w ) of 1.3 times the tube diameter ( D ) was used. Further experimental studies were performed (Wilkinson et al, 2002) on gusset plates slotted into RHS, including those by Martinez and Packer (Martinez-Saucedo et al, 2006; Packer, 2010) on slotted CHS gusset plate connections as well as those by Willibald and Packer (Willibald et al, 2006; Zhao et al, 2008) and Martinez-Saucedo and Packer (2009) on slotted HSS (hollow square section).…”
Section: Introductionmentioning
confidence: 99%